La representación ciudadana de lo público. ¿Punto de partida o de llegada? - Bressan, Catalina (Universidad Nacional del Litoral, 2022)
In this article we analyze participatory public policies within the framework of a reflection on the conditioning of the scale in the citizen representation of the public as the common. We use as study cases the General Participatory Budget and the Young Participatory Budget of the city of Gualeguaychú (Entre Ríos). In methodological terms, it is a qualitative work fundamentally supported by primary sources through in-depth interviews with key actors and direct observation during the popular assemblies of the devices. The secondary sources used are mainly documentary and bibliographic. The hypothesis of the article is that the larger scale positively affects the citizen representation of the public as the common. Conversely, as the scale decreases, the common character of the public becomes fragmented.